Scenario theory philosophy and methodologies - العنزي, سعد; السعيدي, يعرب عدنان (Journal of Economics and Administrative Sciences, 2014)
Purpose: The purpose of this study was to clarify the basic dimensions, which seeks to indestructible scenarios practices within the organization, as a final result from the use of this philosophy.Methodology: The methodology that focuses adoption researchers to study survey of major literature that dealt with this subject in order to provide a conceptual theoretical conception of scenarios theory  .The most prominent findings: The only successful formulation of scenarios, when you reach the decision-maker's mind wa takes aim to form a correct mental models, which appear in the expansion of Perception managers, and adopted as the basis of the decisions taken. The strength lies in the scenarios focus on the outcomes after the event, not the expectation of the event, and the dimensions of the event.Originality and value: To provide an integrated model reflects the philosophy of the theory of scenarios, and how to formulate scenarios according to different intellectual Madras.